Concomitant hip and upper extremity fracture in elderly patients: Prevalence and clinical implications. Issue 11 (November 2019) - Kang, Suk-Woong; Shin, Won Chul; Moon, Nam Hoon; Suh, Kuen Tak
Highlights: We investigated the prevalence and clinical implications of concomitant hip and upper extremity fractures in the elderly. The results of this study showed that cognitive ability and a younger age of the elderly were associated with concomitant upper extremity fracture. Keep in mind that patients with these concomitant fractures have a longer hospital stay and greater difficulty in rehabilitation. Abstract: Background: Hip fracture and upper extremity fracture are most important age-related fracture. However, there have been few reports about the analysis of prevalence or risk factors with concomitant hip and upper extremity fractures. This study aimed to describe the prevalence and clinical implications of the concomitant hip and upper extremity fractures in elderly. Methods: We evaluate 1018 patients aged >65 years who were surgically treated for femoral neck or intertrochanteric fractures between March 2008 and December 2018. 35 patients (3.4%) with a hip fracture combined upper extremity fracture. All patients were classified into the isolated hip fracture and the concomitant fracture. We analyzed these patients' characteristics such as age, gender, bone mineral density (BMD), body mass index (BMI), Korean version of Mini-Mental State Examination (MMSE-K), injury mechanism, and length of hospital stay. Results: The most common site of upper extremity fracture was distal radius fracture of 15 patients (42.8%), followed by proximal humeral fracture of 8 (22.8%). Concomitant fractures occurred on the same side in 30 patients (85.7%). The mean age of patients with a concomitant fracture was younger than that of patients with an isolated hip fracture (p < 0.05). Mean preinjury MMSE-K was 22.7 in isolated hip fracture and 25.6 in concomitant fracture patients (p < 0.05). Mean length of hospital stay was statistically significant different between two groups (p < 0.05). According to fracture site of hip, there was no statistically different prevalence of upper extremity fracture in femoral intertrochanteric fracture compared to the neck fracture. Conclusion: We found a 3.4% prevalence of concomitant hip and upper extremity fractures. It was found that the younger the age with preserved cognitive ability in elderly patients with a hip fracture, the higher the prevalence of upper extremity fracture. In addition, it is important to keep in mind that patients with a concomitant fracture have a longer hospital stay and difficulty in rehabilitation.